Karakteristik Fisikokimia dan Sensoris Snack Bar Tinggi Protein Bebas Gluten dengan Variasi Tepung Beras, Tepung Kedelai dan Tepung Tempe - Binardo Adi Seno Mawarno; Aldila Sagitaning Putri (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
The problem of malnutrition, especially stunting, is still a problem for some Indonesian people because they have not fulfilled both macro and micronutrients in a balanced way. This study aims to determine the quality of protein snack bars that have the potential to overcome stunting problems physically, chemically and sensory. The snack bar formulation in this study used soybean flour, tempeh flour, and a mixture of soybean flour and tempeh flour to substitute for 20% of rice flour. “Granola” in snack bar products is a mixture of crispy rice, tempeh, tofu, nuts and local dried fruits. Data analysis used One Way ANOVA with Duncan and Man Whitney test. The results showed that the snack bar with tempeh flour substitution had the highest protein value of 18.09%. For texture, the snack bar with the addition of soy flour has the most brittle texture, while the sensory analysis results show that the snack bar with the addition of a mixture of soy flour and tempeh is the most preferred by consumers. Overall, all snack bar treatments met the USDA (United States Department of Agriculture) snack bar quality standards, particularly protein values that were well above the minimum value of 8%. Thus, this snack bar product is expected to be one solution to the problem of stunting in children who require high protein intake.